2018
DOI: 10.18203/2349-2902.isj20184646
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and management of locally advanced breast carcinoma

Abstract: Background: Locally advanced breast cancer (LABC) encompasses a heterogeneous collection of breast neoplasia with widely different clinical and biological characteristics. Multidisciplinary therapy has become the treatment of choice for these patients. The present study was undertaken to study the clinical presentation and effects of various modes of management of LABC.Methods: Total 45 patients presented with stage III and inflammatory carcinoma of breast were included in the study and treated with neoadjuvan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…In a study conducted by Gedam et al, clinical presentation and management of locally advanced breast carcinoma majority of patients were in stage IIIA (55.6%) followed by stage IIIB (37.7%). 12 In a study Cance…”
Section: Stage Of the Diseasementioning
confidence: 99%
“…In a study conducted by Gedam et al, clinical presentation and management of locally advanced breast carcinoma majority of patients were in stage IIIA (55.6%) followed by stage IIIB (37.7%). 12 In a study Cance…”
Section: Stage Of the Diseasementioning
confidence: 99%
“…6 Gedam et al in 2018 showed that most of the patients were in the age group of 41-50 years (40%) followed by 31-40 years (33.3%). 7 In our study majority of the patients (98.2%) were females compared to 1.8% males. Vijaya et al in 2020 in 2013 found more preponderance in females (99.8%).…”
Section: Discussionmentioning
confidence: 43%
“…5 In general, male breast cancer incidence trends were variable and a minority of countries showed increasing incidence while female incidence rates showed an increasing trend in a majority of countries. 7 Majority of the females in our study were postmenopausal (66.5%) as compared to premenopausal females (33.5%). Zuo et al 2018 studied that premenopausal patients accounted for 44.5% and postmenopausal patients accounted for 55.5%.…”
Section: Discussionmentioning
confidence: 65%
“…It is the commonest cancer in women and is a leading cause of cancer mortality [1]. Large number of breast cancers in developing countries are locally advanced at presentation (30-60%) [2]. These cancers and a majority of them require NACT to become amenable for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Locally advanced breast cancer (LABC) is the most common presentation in developing countries due to illiteracy, lack of awareness, poor health care, lack of active screening and late presentation. In India, up to 30-35% of breast cancer are locally advanced at the time of presentation [2]. Breast conservation surgery (BCS) is now an acceptable option for women with early-stage breast cancer and even in some cases of locally advanced breast cancer after response to neoadjuvant chemotherapy (NACT) [3][4][5].…”
Section: Introductionmentioning
confidence: 99%